Direct dynamic synthesis of nanodispersed titanium nitride in a high-speed pulse electroerosion plasma jet; Journal of Superhard Materials; Vol. 30, № 5 - Sivkov A. A. Aleksandr Anatolyevich (2008, 2008)
Title screen